(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article describes the problems of phraseology and their structure in the language of the well-known prose writer T.Kaipbergenov "A secret known only to you." In particular, recommendations for solving existing problems are given in the general conclusions. In the process of research special linguistic schemes are identified for grammatical understanding and analysis of the structure of different forms of phraseological compounds specific to the Karakalpak language, reflected in the language of the work of art. The analyzed language units show that in Karakalpak language phraseologies have complex forms in terms of the number of components. In te